Qualidade e conservação pós-colheita de melão em resposta à poda da haste principal e ao raleio de frutos - Ferreira, Rafaella Martins de Araújo (Universidade Federal Rural do Semi-Árido, 2016)
Pruning and thinning are practices that can change the source:sink relations and thus influence the quality and fruit storage capacity. This study evaluated the influence of the pruning of the main stem and the fruit thinning in quality and postharvest conservation of melon. For this, two experiments were conducted, with Galia melon (hybrid Amaregal) and Charentais melon (hybrid Banzai), both with two phases, field and laboratory. In the field, the plants were submitted to the pruning of the main stem and the fruit thinning; the fruits were harvested at 66 and 74 days after sowing (DAS), respectively for Galia and Charentais melon. In the laboratory, the fruits were cleaned, characterized and stored in the freezer. The experiment was conducted in split-plot, and the portion composed of the factorial 2 x 4 + 1: pruning (pruning and unpruning), thinning times (32, 35, 38 and 41 DAS to Galia melon; and 42, 45, 48 and 51 DAS for the Charentais melon) and an additional control (unpruning and unthinning); and the sub-plot was constituted by the storage times (0, 7, 14, 21 and 28 days), with four blocks. The following analyzes were performed: number of fruits per plant (NFP), fruit weight (FW), productivity (PROD), weight loss (WL), external (EA) and internal appearance (IA), epicarp and mesocarp color, flesh firmness (FF), titratable acidity (TA), soluble solids (SS) , total soluble sugars (TSS), reducing sugars (RS) and non-reducing sugar (NRS), and vitamin C (VITC). In the Galia melon, pruning improved the epicarp color and increased the NRS, but reduced the SS. Thinning to 41 DAS depreciated the EA and reduced SS, TSS and NRS, but was positive for epicarp and mesocarp color, and increased VITC. Pruning reduced the TA and the loss in FF at 14 and 28 days of storage, respectively. Pruning associated with thinning to 38 DAS reduced the WL after 28 days of storage and result in an increased RS. In storage was observed decreasing in EA, IA, SS, RS, NRS, TSS and VITC. In the Charentais melon, the pruning reduced WL to 28 days of storage. Pruning also decreased TA. The treatments with pruning and thinning positively influenced the fruit epicarp color. Thinning to 42 DAS increased the SS and SS/TA ratio. In storage period there was a reduction in EA, IA, FF, TA, RS, VITC and increase in SS, SS/TA ratio, TSS and NRS
Quality and postharvest conservation of melon in response to pruning of main stem and fruit thinning
Keywords: Cucumis melo L; Poda; Raleio; Armazenamento; Cucumis melo L; Pruning; Thinning; Storage; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA